Quantum dynamics in cavity-coupled molecules: numerical simulations and applications - (:unkn) unknown (My University, 2026)
Experimental breakthroughs are currently driving the young research field of molecular polaritonics. It has been shown that the physics and the chemistry of molecular ensembles can be drastically modified by a collective coupling to a cavity, also for a cavity-mode close to its vacuum, and at room temperature. In the last few years, pioneering experiments have e.g. demonstrated modified chemical reactivity, enhanced charge conductivity, and lately even improved critical temperatures for superconductivity. Due to those rapid experimental advances, new theory approaches are in great demand. Current methods are typically limited to small systems, low excitation numbers, or mean-field assumptions. This theory project explores quantum dynamics in molecular polaritonics, from a numerical quantum optics perspective. Specifically, this project will study collective molecular quantum many-body dynamics and its impact on cavity-enhanced molecular formation/chemistry, and analyze the modifications of scattering properties in cavities. Our studies will be enabled by the development of novel numerical methods. The PI in Chile is a leading expert in cavity-controlled chemistry, while the PI in France has recently developed novel numerical ideas to tackle strongly-correlated quantum many-body physics. The goal of this bilateral project is to exchange expertise in order to employ new numerical approaches in polaritonic chemistry.
Keywords: MOLECULAR PHYSICS AND CHEMICAL PHYSICS; QUANTUM ELECTRODYNAMICS (QED); QUANTUM OPTICS